DEVELOPING TEACHERS' CREATIVITY THROUGH SELF-REGULATION METHODS - Gevorgyan, Astghik (Modern Psychology, 2025)
The article explores how mindfulness meditation, as a psychological self-regulation method, can develop theachers creative thinking. It reviews different perspectives on creativity and emphasizes the psychological and psychophysiological connections between mindfulness and creativity. The primary objective of the study was to investigate the effects of self-regulation methods on the growth of creativity of the teachers.Research methods were testing and experiment. The results of the applied methods were analysed by correlation and paired sample t-test. The correlation analysis revealed significant relationships between various mindfulness components and criteria of creative thinking, as well as characteristics of a creative individual. The paired sample t-test results of the experimental training largely confirmed the identified correlations. Participants demonstrated considerable improvements in creative thinking and its criteria, such as flexibility, originality, elaboration, and creative speech. Both correlation and training results analysis showed, that increase in the nonjudging of inner experience, a factor of mindfulness, improved elaboration and increase in the nonreactivity to inner experience, a factor of mindfulness, improved complexity, individual characteristic of a creative individual.In conclusion, the results of the theoretical and experimental research suggest that integrating mindfulness practices, particularly during the incubation and insight phases of the creative process, can effectively develop creative thinking, the emergence of insight and creative solutions among teachers.The novelty of this scientific research is that the psychological and psychophysiological connections between creativity development and psychological self-regulation methods are presented. The data of the experimental research conducted based on such revealed connections makes it possible to confirm that mindfulness meditation can be used in the process of creativity development.
Keywords: Creative thinking; creativity; mindfulness meditation; teachers; teaching creatively